Os jogos e as brincadeiras nas aulas de educação física : concepções de professores sobre suas implicações lúdicas - Alvarenga, Thaís Caroline de Pinho (2020)
Play, toys and games are historical constructions, marked by transformations and changes suffered over the centuries. Current models of civilization indicate changes in the spaces of children, childhood, society and the education of the little ones. We live in a time marked by social and cultural constructions and reconstructions, which directly influence the child's imagination and play. Each area of education has its conception and objective ambition of play, as for example, educators tend to expect play to benefit students' socialization or development; communication theorists center play as a form of metacommunication. Hence studying games and play is more complex than it seems. We may have to approach the meanings that play has for the child, respecting this content as an important factor for culture production, so it is necessary to think this content in the school environment, how these activities are being developed and used in school. That said, the guiding problem of this study was formulated as follows: How do Physical Education teachers work games and play in school, and what playful implications can this content offer us? Thus this study aimed to understand the conceptions that Physical Education teachers of the municipal network of Cuiabá have about games and games as playful manifestations and their implications in the early years of elementary school. A qualitative descriptive research was developed with two Physical Education teachers working in the early years of elementary school in schools of the municipal public school in Cuiabá-MT. This research has ethnographic characteristics, we adopted as data collection instrument: Document analysis; Semi-structured interview with teachers of Physical Education and Systematic Observation of the 1st class. and 2nd. elementary school years by their teachers. The analysis was performed based on the construction of three descriptive categories. The data reveal that teachers understand games and play as part of the children's universe, but still have difficulty in relating the spaces / time of play in school, restricting the use of playgrounds and school recess. In the Work Plan, teachers adopt the concept of “learning for pleasure”, that is, pleasure would facilitate the acquisition of knowledge and skills. The scarcity of material and lack of basic infrastructure directly influenced the quality of the developed classes, however, the teachers sought to adapt the necessary, so that the students had their time to play during the Physical Education class. As for the playful implications, we realize that they are present in each teacher's classes, even unintentionally, covered the characteristics of motor, affective, moral, intellectual and symbolic implications. The teachers recognize games and play as a significant content of Physical Education classes, as well as their relationship with the child. We hope this research will help teachers, higher education institutions and schools to reflect and give greater visibility to this content.